2015
DOI: 10.1093/jhps/hnv011
|View full text |Cite
|
Sign up to set email alerts
|

Subtrochanteric osteotomy for femoral mal-torsion through a surgical dislocation approach

Abstract: Missed torsional femur deformities may contribute to reasons for failure after open and more likely arthroscopic hip preservation surgery. A number of surgical approaches have been described for addressing torsion abnormalities. This report describes a subtrochanteric osteotomy technique in a consecutive series of patients with complex hip pathologies, for which intertrochanteric osteotomy is not suitable and precise derotation is required. Subtrochanteric derotation was performed, always in combination with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 46 publications
0
55
1
Order By: Relevance
“…A subtrochanteric derotation femoral osteotomy may also be performed by plating, but it requires a much more invasive approach. 40 The advantage of the described technique is that it allows for a much less invasive approach, lessening surgical morbidity and theoretically a lower chance of infection. In addition, the vastus lateralis is not dissected from the femur, maintaining more of the periosteal blood supply to enhance bone union.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subtrochanteric derotation femoral osteotomy may also be performed by plating, but it requires a much more invasive approach. 40 The advantage of the described technique is that it allows for a much less invasive approach, lessening surgical morbidity and theoretically a lower chance of infection. In addition, the vastus lateralis is not dissected from the femur, maintaining more of the periosteal blood supply to enhance bone union.…”
Section: Discussionmentioning
confidence: 99%
“…Kamath et al 40 reported 28 rotational femoral osteotomies in 26 patients, 93% for excessive femoral anteversion. Clinical outcomes were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Derotational osteotomies have been used to correct femoral retrotorsion and have been shown to decrease pain associated with impingement. The premise used in our model was that if derotation can correct retroversion, a rotational osteotomy should be able to produce retroversion [ 30 ]. Matsuda et al [ 27 ] corrected femoral retroversion in their case report by doing bilateral proximal femoral derotational osteotomies.…”
Section: Discussionmentioning
confidence: 99%
“…A 300-lb load was chosen as an approximation of the joint reaction force one might experience in rising from or lowering into a chair [ 24 ]. Proximal femoral and subtrochanteric osteotomies have been used to correct retroversion/retrotorsion in FAI [ 27 , 30 , 31 ]. Thus, a subtrochanteric osteotomy was chosen for this model as it was easily reproducible, retroversion could be calibrated and the osteotomy could be rigidly fixed.…”
Section: Discussionmentioning
confidence: 99%
“…18 Intraoperatively it is possible to test for full range of motion (ROM) before performing acetabular osteoplasty or to opt for a subtrochanteric derotation osteotomy if needed. 59 Surgical hip dislocation also allows for a full labrum reconstruction using fascia lata, hamstrings tendons, or ligamentum teres. 26,60 At the end of the procedure the capsule should be partially closed to avoid intra-articular increased pressure from cancellous bone bleeding.…”
Section: Surgical Techniquementioning
confidence: 99%